Case report: Traumatic ventricular aneurysm combining tricuspid valve avulsion in a child: Diagnostic findings and treatment protocols - Zhang, Dengshen; Wei, Shan; Tao, Wenhong; Liao, Yuanfeng; Xiao, Ruihan; Liu, Daxing (Frontiers in Cardiovascular Medicine, 2022)
This case report is an extremely rare case of a traumatic left ventricular aneurysm in a 3-year-old child who also suffered avulsion of the tricuspid valve due to blunt trauma. Diagnostic findings and treatment protocols are discussed to provide a clinical reference.